Mathematical study of neural feedback roles in small target motion detection - Ling, Jun; Wang, Hongxin; Xu, Mingshuo; Chen, Hao; Li, Haiyang; Peng, Jigen (Frontiers in Neurorobotics, 2022)
Building an efficient and reliable small target motion detection visual system is challenging for artificial intelligence robotics, because a small target only occupies few pixels and hardly displays visual features in images. Biological visual systems that have evolved over millions of years could be ideal templates for designing artificial visual systems. Insects benefit from a class of specialized neurons, called small target motion detectors (STMDs), which endow them with excellent ability to detect small moving targets against cluttered dynamic environment. Some bio-inspired models featured in feed-forward information processing architectures have been proposed to imitate functions of the STMD neurons. However, feedback, a crucial mechanism for visual system regulation, has not been investigated deeply in the STMD-based neural circuits and its roles in small target motion detection remain unclear. In this paper, we propose a time-delay feedback STMD model for small target motion detection in complex background. The main contributions of this study are as follows. First, a feedback pathway is designed by transmitting information from output-layer neurons to lower-layer interneurons in the STMD pathway and the role of the feedback is analyzed from the view of mathematical analysis. Second, to estimate the feedback constant, the existence and uniqueness of solutions for nonlinear dynamical systems formed by feedback loop are analyzed via Schauder's fixed point theorem and contraction mapping theorem. Finally, an iterative algorithm is designed to solve the nonlinear problem and the performance of the proposed model is tested via experiments. Experimental results demonstrate that the feedback is able to weaken background false positives while maintaining a minor effect to small target. It outperforms existing STMD-based models regarding the accuracy of fast-moving small target detection in visual clutter. The proposed feedback approach could inspire the relevant modeling of robust motion perception robotics visual systems.